The transformation of dbr2 and p19 Genes into Artemisia annua L. by Agrobacterium tumefaciens Mediation: Metabolites Analysis - Sy, Khairunnisa; Kristianti, Tati; Suhandono, Sony; Elfahmi, Elfahmi (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The low level of Artemisinin in Artemisia annua L. is associated with its biosynthetic pathway. Genetic engineering offers a potential solution to increase its metabolites. The research objectives were to transform the double bond reductase (dbr2), one of the critical genes in the biosynthesis of Artemisinin, and p19, an anti-silencing gene, into A. annua L. by the mediation of Agrobacterium tumefaciens and assess their impact on metabolites production. The dbr2 and p19 genes were verified by analyzing PCR products. Plasmids pCAMBIA1303-DBR2-P19 were transformed into A. tumefaciens and subsequently introduced into the leaves from tissue culture of A. annua L, using vacuum infiltration and assessed by GUS assay. UPLC-ESI-MS/MS measured artemisinic acid (AA), dihydroartemisinic acid (DHAA), and Artemisinin contents. The transformation in A. tumefaciens was successful using a freeze-thaw method. The tissue culture of A. annua L. has been infected by A. tumefaciens using vacuum infiltration. Based on the GUS histochemical assay, the gene has been successfully inserted in the leaves with an efficiency of 48.2%. The result from UPLC-ESI-MS/MS showed that the level of Artemisinin in the transformation sample with and without pCAMBIA-dbr2-p19 was detected but not quantifiable while in wild-type leaves were quantified at 0.008% in fresh weight. The AA and DHAA were not detectable but only in the wild type. The transformation was successful, but the quantification of DHAA and AA was unsuccessful because of the low quantity in the samples.